The Use of Plant Bioactive Compounds to Mitigate Enteric Methane in Ruminants and its Application in Indonesia - Elizabeth Wina (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2012)
Worldwide, increasing greenhouse gas (GHG) emissions have become a major concern as they are now considered to be the cause of global warming. Several strategies have been planned and taken by different countries including Indonesia to mitigate this situation. Agriculture is considered to be one of major contributors to GHG, especially methane coming from ruminant digestive processes. More than 85% of the methane produced by ruminants comes from enteric fermentation. Several options have been proposed to lower this enteric methane production. This paper describes a review on diet manipulation using feed additives, especially plant bioactive compounds, to mitigate the GHG emission from ruminant livestock. Plant bioactive compounds  have  been  found  with  various  chemical structures.  Some  of  them  such  as  saponin,  tannin, essential oils, organosulphur compounds, have been reported to have ability to reduce enteric methane production. Indonesia has many plant resources that have potential as methane reducing agents. Sapindus rarak fruit especially its methanol extract contain saponins which reduce the activity of methanogens in the rumen in vitro, hence reduce methane production (11%). Feeding S. rarak to sheep increased daily weight gain but not that of local cattle. Shrub legumes such as Calliandra calothyrsus and Leucaena leucocephala contain tannins which can reduce methanogenesis (3 – 21% methane reduction). Besides tannin, these shrub legumes are a good source of protein. Feeding shrub legumes can be beneficial as a protein source and a methane reducer. Other sources of methane reducing agents have been tested in other countries and some can be applied for Indonesian situation. The strategy to reduce methane by plant bioactive compounds should be developed to be simple and relatively cheap so it will benefit the local farmers. Extraction of these compounds  may be expensive, therefore, costs should be considered carefully when proposing to use the extract as a feed additive for livestock raised by small farmers. It is recommended to develop a feeding system for ruminant using tannin containing plants/ legumes, saponin containing plants or other plants.   Key words: Bioactive compounds, methane, ruminant